Between Agency and Exploitation:: Historiographical Reflections on Children and Adolescents in the Worlds of Adult Labor in Brazil (TEL Tempo, Espaço e Linguagem, 2026)
The article analyzes the historiography of childhood and youth focused on children and adolescents in the world of adult labor in Brazil. Guided by the social history of labor and the sociology of childhood, it discusses the transition from the view of children as passive subjects to historical subjects (“child actors”). Through a literature review, it examines class dynamics and children's agency in relation to capital, aiming to deconstruct adult-centric perspectives in the historical study of the early exploitation of children and adolescents in the adult world of work.